Long-Term Impacts of Short Exposure to Conditional Cash Transfers in Adolescence : Evidence from the Philippines - Dervisevic, Ervin (World Bank, Washington, DC, 2021)
This paper evaluates the long-term impacts of the national conditional cash transfer program in the Philippines on beneficiaries who were exposed to it during a relatively short but potentially critical period of transitioning from adolescence to adulthood. The paper estimates the impacts of the Pantawid Pamilyang Pilipino Program on men and women who were enrolled in the program for up to 1.5 years when they were between ages 12.5 and 14 and are currently in their early twenties. The analysis finds evidence of impacts on marriage and fertility for women: participation in the program is associated with delay in marriage and the first birth of approximately one year and six months, respectively. No impacts are found on educational or labor market outcomes or proxies for economic welfare. Further, there is no strong and consistent evidence of changes in empowerment or gender norms.